Assessing the flavour stability of lager-style beers - Maxminer, Joerg (2016)
Beer, as manufactured, is not at chemical equilibrium and undergoes complex chemical reactions during storage which can lead to undesirable changes in the sensory characteristics of beer. Since beer contains more than 600 volatile compounds, beer flavour change is a complex field of research and the dependable prediction of shelf life remains a top research priority. Chapter 1 places the work described in this thesis into this context. Chapters 2 and 3 provide details of the experimental methods used and their development, respectively, to evaluate flavour stability. The methods used and developed include: (i) the determination of one of the major antioxidants present in beer, sulphur dioxide (SO2), via distillation; (ii) a solid phase micro extraction (SPME)-GC-MS method with on fibre derivatization as a reliable detection method for aldehydes related to off flavours perceived in aged beer; (iii) measurement of the oxidative stability using electron paramagnetic resonance (EPR) spectroscopy. Chapter 4 describes oxidative stability measurements via EPR spectroscopy for three different lager-style beer qualities pre- and post-filtration. The trial included a large scale Kieselguhr frame filter, and two pilot-scale membrane filtration system. The results illustrate how EPR spectroscopy is sensitive to metal ion pick-up from traditional filter media and oxidative stability measures were evaluated versus oxygen pick up during filtration and sulphur dioxide content of the beer samples. The effect of a brewhouse addition of gallotannins on the flavour stability of a lager-style beer was investigated in Chapter 5. Pilot scale (16 hl) and large scale production line (1500 hl) experiments with gallotannins additions in the Brewhouse were performed. The effects of the different additions were monitored at key points of the production process and through to the final beer. Despite showing significant improvements in the pilot scale wort samples, the results for the related packed beer samples did not show clear flavour stability improvements. For the production-scale trials, only a very limited effect of improved flavour stability could be observed. In Chapter 6 a factorial experimental design was adopted to probe the interactions between seven factors known to impact on beer flavour stability. Chemical additions were made to a bright beer prior to bottling, to vary the following factors: total in pack oxygen, SO2, total iron, iso-α-acid and α-acid content, (+)-catechin and glutathione. Increased SO2 concentrations had the largest impact across the entire design space, resulting in reduced radical formation, staling aldehyde concentrations and improved sensory scores. The impacts of increased TIPO levels were rather limited. In contrast, a significant impact regarding the oxidative stability could be observed for increasing Fe concentration, highlighting the significance of pro-oxidative effects of transition metals.